A Systematic Review of CTML Segmenting Principle on Computational Thinking - Wan Nor Ashiqin Wan Ali; Wan Ahmad Jaafar Wan Yahaya, (Journal of Human Development and Communication (JoHDeC), 2025)
This paper reviews systematically articles and journals in the past and current studies on Cognitive Theory of Multimedia Learning (CTML) segmenting principle and computational thinking. This paper specifically conducted to (i) identify articles that discussed computational thinking (CT) and segmenting principle, (ii) classify the various research domain and context are discussed in previous studies related to segmenting on CT, (iii) synthesis the results that are reported by relevant studies on CT and segmenting principle. The steps taken for these systematic reviews are adapted from PriSMA (2009). Out of 231 articles retrieved, 22 of them were identified for analytical purposes in tandem with the observed theme under keywords searched “computational thinking AND segmenting” and then, those articles are thoroughly reviewed. Our study revealed that the use of CT is most discussed on the programming and science, technology, engineering, and mathematics (STEM) subjects. Furthermore, this paper pointed out and highlighted that most of the reviewed articles are not related to the segmenting principle even though they are listed as the results of the keywords searched.